Critical switching current density of magnetic tunnel junction with shape perpendicular magnetic anisotropy through the combination of spin-transfer and spin-orbit torques - Kang, Doo Hyung; Shin, Mincheol (Scientific reports, 2021)
Recently, magnetic tunnel junctions (MTJs) with shape perpendicular magnetic anisotropy (S-PMA) have been studied extensively because they ensure high thermal stability at junctions smaller than 20 nm. Furthermore, spin-transfer torque (STT) and spin-orbit torque (SOT) hybrid switching, which guarantees fast magnetization switching and deterministic switching, has recently been achieved in experiments. In this study, the critical switching current density of the MTJ with S-PMA through the interplay of STT and SOT was investigated using theoretical and numerical methods. As the current density inducing SOT ( J SOT ) increases, the critical switching current density inducing STT ( J STT,c ) decreases. Furthermore, for a given J SOT , J STT,c increases with increasing thickness, whereas J STT,c decreases as the diameter increases. Moreover, J STT,c in the plane of thickness and spin-orbit field-like torque ( β ) was investigated for a fixed J SOT and diameter. Although J STT,c decreases with increasing β , J STT,c slowly increases with increasing thickness and increasing β . The power consumption was investigated as a function of thickness and diameter at the critical switching current density. Experimental confirmation of these results using existing experimental techniques is anticipated.